Emissão de CO2 do solo em áreas de restauração na Mata Atlântica - Castellano, Gabriel Ribeiro [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In order to improve the knowledge about the carbon balance in the Atlantic Forest biome, the characterization of soil carbon dioxide (CO2) emissions is a priority associated to its correlation with environmental variables, and the soil chemistry, physical and biological properties. This study aims to quantify the CO2 emission rates from the soil in two forested areas, stablished over Red Ultisol, located in the morphoclimatic domain of Atlantic Forest, in the municipality of Rio Claro-SP. The CO2 emission rates were correlated to atmospheric variables and physical and chemical parameters of the soil, such as air pressure, air and soil temperature and humidity, soil thermal conductivity, and the C/N ratio. Finally develop a statistical model of multiple linear regression for prediction of soil respiration under these conditions. The study area is located in a sustainable conservation area, the State Forest Edmundo Navarro de Andrade (FEENA). The measurement of CO2 emissions was performed using an infrared gas analyzer (IRGA), Li-840 model of Li-Cor brand, coupled to a dynamic chamber by means of a circulation pump, in two areas under different regeneration levels, located in FEENA: plot 23 was planted in 1916, and plot 15 planted in 2014. To measure the CO2 emissions a portion up to 900 m² were demarcated, and within each study area installed 17 measuring points. The soil CO2 emission in plot 15, during summer 2014, ranged from 0,51 mol CO2 m-2s-1 up 2,59 mol CO2 m-2s-1 (average 1.38 mol CO2 m-2s-1) with a significant positive linear correlation with the thermal conductivity (r=0.56, p<0.0001), the C/N ratio (r=0.28, p<0.05), and with the time (r=0.33, p<0.05). Plot 23 soil respiration range between 0.61 mol CO2 m-2s-1and 3.86 mol CO2 m-2s-1(average 1.91 mol CO2 m-2s-1), presenting a significant linear correlation with soil moisture (r=0.55, p<0.0001) and air humidity (r=0.28, p<0.05). The average emissions, considering...

Para o entendimento do balanço de carbono no bioma da Mata Atlântica é prioritária a caracterização das emissões de gás carbônico (CO2) pelo solo, bem como sua correlação com as variáveis ambientais e as características químicas, físicas e biológicas do solo. O presente estudo teve como objetivo principal caracterizar as taxas de emissão de CO2 no solo, em duas áreas florestais, sobre Argissolo vermelho, dentro do domínio morfoclimático da Mata Atlântica, na Floresta Estadual Edmundo Navarro de Andrade (FEENA), situada no município de Rio Claro - SP. Acrescenta-se ainda a correlação dessas emissões com parâmetros atmosféricos e do solo: pressão, temperatura do ar e do solo, umidade do ar e do solo, condutividade térmica do solo, e a relação C/N, que permitiram a elaboração de um modelo estatístico de regressão linear múltipla para predição da respiração do solo nestas condições. A mensuração dos fluxos de CO2 foi realizada em duas áreas na FEENA localizadas no talhão 23, implantado no ano de 1916, e no talhão 15 reflorestado no ano de 2014. Para as medições foi utilizado um analisador de gás infravermelho (IRGA), modelo Li-840 da marca Li-Cor, acoplado a câmara dinâmica, por meio de bomba de circulação. Em cada área foi instalada uma parcela amostral de 900 m², e dentro delas foram instalados 17 pontos de medição. As emissões de CO2 na área recém reflorestada do talhão 15 variaram entre 0,51 e 2,59 mol CO2 m-2s-1 (média de 1,38 mol CO2 m-2s-1), apresentando correlação linear positiva com a condutividade térmica (r=0,56, p<0,0001), a relação C/N (r=0,28, p<0,05) e o com o horário da coleta (r=0, 33, p<0,05). Já no talhão 23, as emissões variaram de 0,61 a 3,86 mol CO2 m-2s-1 (média de 1,91 mol CO2 m-2s-1), apresentando correlação linear significativa com a umidade do solo (r=0,55, p<0,0001) e a do ar (r=0,28, p<0,05). Considerando as duas áreas mensuradas...
Keywords: Floresta Estadual Edmundo Navarro de Andrade (Rio Claro, SP); Soil science; Ciência do solo; Florestas - Restauração; Carbono; Solos - Carbono; Mata Atlântica